"Comparison of cardiovascular autonomic activity (heart rate variability and baroreceptor sensitivity) in young healthy females during fasting and hyperglycaemia". Issue 5 (September 2020) - Majeed, Farrukh; Yar, Talay
Abstract: Background and Aim: The present study compared cardiovascular autonomic activity and reactivity during fasting (FS) and hyperglycemia (HS) states in young healthy females. Methods: This case crossover study was conducted on 30 females recruited by convenient sampling. Blood glucose levels were measured in FS and after oral glucose load i.e., HS. Finger arterial blood pressure (BP) and ECG were recorded constantly to monitor baroreceptor sensitivity (BRS) and heart rate variability (HRV). Autonomic reactivity was tested with deep breathing (DB), Valsalva manoeuvre (VM), and head-up-tilt (HUT) test under FS and HS. HRV parameters not normally distributed were natural log (ln) transformed. Results: Significantly reduced Valsalva ratio and higher heart rate and BP were observed in HS that continued during HUT (P < 0.05). The lnSDNN (standard deviation of normal-to-normal intervals) and lnRMSSD (root mean square of successive differences) were significantly lower (p < 0.05) in HS during HUT. After HUT, lnRMSSD remained lower (P = 0.031), whereas lnLF/HF (low frequency/high frequency power) ratio (P = 0.042) and LFnu (normalized units) (P = 0.024) were higher in HS. BRS was significantly lower in supine position in HS compared to FS and further reduced in HUT position in both FS and HS (P < 0.05). Conclusion: Compared to FS, the HS exhibited heightened sympathetic activity with attenuation of parasympathetic activity and this phenomenon was further accentuated by HUT. BRS was more sensitive indicator of autonomic effects of hyperglycemia in resting state. In addition to standard tests, autonomic reactivity in vulnerable young subjects could be useful to detect autonomic imbalance at an early stage. Highlights: First study to compare cardiovascular autonomic activity & reactivity in healthy young females in fasting & hyperglycemia Valsalva ratio & baroreceptor sensitivity at rest were significantly lower in hyperglycemic compared to fasting state Resting heart rate variability & response to deep breathing exhibited no differences in fasting and hyperglycemic states Heart rate variability in head up tilt test exhibited significant differences between the fasting & hyperglycemic states